2017
DOI: 10.1590/s1982-21702017000100014
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Improve Geocentric Translation Model Performance Using Artificial Neural Network Technology

Abstract: Abstract:Geocentric translation model (GTM) in recent times has not gained much popularity in coordinate transformation research due to its attainable accuracy. Accurate transformation of coordinate is a major goal and essential procedure for the solution of a number of important geodetic problems. Therefore, motivated by the successful application of Artificial Intelligence techniques in geodesy, this study developed, tested and compared a novel technique capable of improving the accuracy of GTM. First, GTM b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…From a practical point of view, the testing results produced by the proposed LS-SVM and the widely used BPNN and RBFNN are satisfactory for cadastral surveying applications in Ghana. This statement is buttressed by the ±0.914 m tolerance residual distance set by the Ghana Survey and Mapping Division of Lands Commission for its cadastral surveying works (Yakubu & Kumi-Boateng, 2015;Ziggah, Youjian, Laari, & Hui, 2017). Therefore, the quantitative results presented in Table 4 affirm that assertion.…”
Section: Test Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…From a practical point of view, the testing results produced by the proposed LS-SVM and the widely used BPNN and RBFNN are satisfactory for cadastral surveying applications in Ghana. This statement is buttressed by the ±0.914 m tolerance residual distance set by the Ghana Survey and Mapping Division of Lands Commission for its cadastral surveying works (Yakubu & Kumi-Boateng, 2015;Ziggah, Youjian, Laari, & Hui, 2017). Therefore, the quantitative results presented in Table 4 affirm that assertion.…”
Section: Test Resultsmentioning
confidence: 66%
“…Numerous studies have shown successful implementation of ANN in the geodetic disciplines including but are not limited to deformation studies (Li & Kong, 2014;Huang, Wu, & Ziggah, 2016), meteorological studies (Mohammadi et al, 2015;Durmaz & Karslioglu, 2011), hydrological studies (Tiwari, J. Adamowski, & K. Adamowski, 2016;Deo & Şahin, 2016;Deo, Tiwari, Adamowski, & Quilty, 2017), tidal estimation (Okwuashi & Ndehedehe, 2017), change detection (Pal, 2009;Chang, Han, Yao, Chen, & Xu, 2010), geoid determination (Kavzoglu & Saka, 2005;Sorkhabi, 2015), and gravity field modelling (Turgut, 2016). Additionally, extensive studies on the suitability of ANN for coordinate transformation in both 2D and 3D have also been duly investigated by several authors (Tierra et al, 2008;Zaletnyik, 2004;Lin & Wang, 2006;Tierra, De Freitas, & Guevara, 2009;Tierra & Romero, 2014;Gullu, 2010;Gullu et al, 2011;Turgut, 2010;Mihalache, 2012;Yilmaz & Gullu, 2012;Konakoğlu, Cakir, & Gökalp, 2016;Ziggah, Youjian, Tierra, Konate, & Hui, 2016;Kumi-Boateng & Ziggah, 2017). A thorough review of these coordinate transformation studies indicates that the ANN of radial basis function and backpropagation have been the most commonly used techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Notable among them is the three-dimension (3D) conformal transformation models like Bursa-Wolf (Bursa, 1962;Wolf, 1963), Molodensky-Badekas (Molodensky et al, 1962;Badekas, 1969), Abridged Molodensky (Molodensky et al, 1962) and Veis (Veis, 1960). Conversely, in recent times, artificial neural network (ANN) techniques have also been applied for coordinate transformation (Gullu, 2010;Gullu et al, 2011;Lin and Wang, 2006;Mihalache, 2012;Tierra et al, 2008Tierra et al, , 2009Tierra and Romero, 2014;Turgut, 2010;Yilmaz and Gullu, 2012;Zaletnyik, 2004;ElSayed and Ali, 2016;Ziggah et al, 2016;Ziggah et al, 2017a). It was, however, evident in literature that, the statistical test called the hold-out cross-validation has been the most commonly used technique to evaluate coordinate transformation models performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the data is quite small, the hold-out cross-validation procedure was implemented where 20 co-located points were used to form the model and 7 evenly distributed points were used to test the model. In addition, Ziggah et al (2017a) developed an error compensation model based on ANN capable of improving the performance of the geocentric translation model. Here, 19 co-located points were divided into 11 training points and 8 testing points, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ziggah et al (2016b) investigated the 3D coordinate transformation performance of the multilayer feed-forward (MLF) neural network, the radial basis function neural network (RBFNN), and multiple linear regression (MLR) and reported that all methods presented satisfactory results. Ziggah et al (2017) proposed a novel approach to improve the geocentric translation model performance based on the MLF neural network, the RBFNN, and the generalized regression neural network (GRNN). The proposed model ANN-ECM (Artificial Neural Network-Error Compensation Model) was found to achieve better transformation accuracy than the geocentric transformation model.…”
Section: Introductionmentioning
confidence: 99%